"We Won't Retire Without Skeletons in the Closet": Healthcare-Related Regrets Among Physicians and Nurses in German-Speaking Swiss Hospitals. (September 2018) - von Arx, Martina; Cullati, Stéphane; Schmidt, Ralph E.; Richner, Silvia; Kraehenmann, Rainer; Cheval, Boris; Agoritsas, Thomas; Chopard, Pierre; Burton-Jeangros, Claudine; Courvoisier, Delphine S.
Physicians and nurses are expected to systematically provide high-quality healthcare in a context marked by complexity, time pressure, heavy workload, and the influence of nonclinical factors on clinical decisions. Therefore, healthcare professionals must eventually deal with unfortunate events to which regret is a typical emotional reaction. Using semistructured interviews, 11 physicians and 13 nurses working in two different hospitals in the German-speaking part of Switzerland reported a total of 48 healthcare-related regret experiences. Intense feelings of healthcare-related regrets had far-reaching repercussions on participants' health, work-life balance, and medical practice. Besides active compensation strategies, social capital was the most important coping resource. Receiving superiors' support was crucial for reaffirming professional identity and helped prevent healthcare professionals from quitting their job. Findings suggest that training targeting emotional coping could be beneficial for quality of life and may ultimately lead to lower job turnover among healthcare professionals.